Current and future role of methotrexate in the therapeutic armamentarium for rheumatoid arthritis. (April 2012) - Kaltsonoudis, Evripidis; Papagoras, Charalampos; Drosos, Alexandros A
Methotrexate (MTX) has been used for rheumatoid arthritis (RA) treatment since 1980. It is the most common effective disease-modifying antirheumatic drug (DMARD) for RA, and is considered to be the anchor drug, to which other DMARDs or biological agents are added to, in order to achieve an optimal therapeutic effect. MTX improves signs and symptoms to a similar degree as anti-TNF agents. However, it seems to inhibit radiographic progression less effectively than anti-TNF agents. The appropriate route of administration and optimal dose should be individualized depending on the profile and response of the patient. It seems to be one of the safest DMARDs, while there is evidence that patients treated with MTX have lower mortality, especially due to cardiovascular causes. Currently, there is no reliable way to predict which patients will respond to treatment with MTX, and who will experience side effects, the answer to which remains to be clarified.